Caracterización geológica y geotécnica de la vía antigua a Cuenca tramo el Gallo – Naranjo del cantón y provincia de Loja - Cevallos Valencia, Maritza Fernanda (2023)
The objective of the current research work is to carry out the geological and geotechnical characterization of the old road to Cuenca, El Gallo – Naranjo section, located in the canton and province of Loja, in an area of 3 km, covering an area of 58.18 ha. First, the topographic survey was developed with an unmanned aerial vehicle (drone) at a scale of 1:5000, which served as the basis for the preparation of the local geological map made from the information collected in the description of 11 outcrops. In addition, an inventory of 10 mass movements along the section was carried out. Once the local lithology was identified, 3 VES were carried out close to the critical landslides, 1 geotechnical pit test on the crown of the old landslide MM1, 1 direct shear test carried out on the crown of the representative landslide MM4 and the geomechanical characterization of 9 rock masses. Four representative rock slopes were selected from which rock samples were extracted to analyze them in the laboratory and determine the physical-mechanical properties. They were also characterized using the RQD, RMR, SMR and GSI systems and the kinematic analysis was developed for the case of planar and wedge breakage in the Dips 7.0 software. The cohesion and friction angle were obtained from the resistance analysis carried out in the Roclab software under the Hoek and Brown criterion adjusted to the Mohr-Coulomb criterion. Finally, with the geological, geomechanical and geotechnical characteristics of the 4 representative rock slopes and MM4 landslide, the safety factor was calculated in the Slide v5.0 Software using the limit equilibrium methodology: Bishop simplified, Janbu simplified, and Spencer method, obtaining for rock slope N°1, N°2 and N°4 stable safety factors > 1.5, for rock slope N°3 a critical SF of 1.52 and for the MM4 slide an unstable SF of 0.93. Keywords: geomaterials, representative rock slope, landslides, resistance parameters, safety factor.